Echocardiography: An Important Tool for Diagnosis, Guidance of Intervention and Post- Interventional Follow Up of the Congenital and Structural Heart Diseases - Begum, NNF; Razzaque, AKM; Rahman, MM (Cardiovascular Journal, 2012)
DOI: http://dx.doi.org/10.3329/cardio.v4i1.9393 Cardiovasc. J. 2011; 4(1): 67-74